IMPLEMENTING CHARACTER EDUCATION IN ELEMENTARY SCHOOL: A QUALITATIVE STUDY AT SDN 064025 TANJUNG SELAMAT MEDAN - Enjelia Sihite; Meikardo Samuel Prayuda; Maria Sihotang (Pustaka Karya Mandiri, 2025)
Character education is an essential component of elementary education because it shapes students’ moral awareness, social behavior, discipline, responsibility, and respect for others. In the context of elementary schools, character formation cannot be separated from daily classroom practices, teacher modeling, school culture, family support, and students’ habituated behavior. This study aims to describe the implementation of character education at SDN 064025 Tanjung Selamat Medan and to identify the character values developed through school-based practices. This study employed a descriptive qualitative method. Data were collected through observation, teacher interviews, and documentation from May 14 to June 14, 2025. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that character education was implemented through four main forms: responsibility, respect, caring, and habituation. These forms were reflected in students’ daily behavior, such as maintaining school cleanliness, completing assignments, arriving at school on time, respecting teachers and peers, helping friends in need, praying before and after lessons, and greeting others politely. The implementation of character education was supported by teachers, family involvement, and the surrounding community. However, limited parental attention at home became one of the inhibiting factors. The study concludes that character education at SDN 064025 Tanjung Selamat contributes to shaping students who are responsible, disciplined, diligent, caring, and religious.